Sunburst - Warren, Susan May, 1966- (Warren, Susan May, 1966- Sky King ranch, 2022)
When former Navy Seal Ranger Kingston rescues his kidnapped brother, he discovers among the hostages a woman he once promised to protect. But protecting Noemi Oyoma Sutton this time will require a marriage of convenience--which is decidedly inconvenient if she is to protect him from a deadly secret.--